The Old Vero Site (8IR009) one hundred years later, the 2014-2017 excavations - Adovasio, James M. 1944-; Hemmings, C. Andrew 1967-; Vento, F. J.; Duggan, John S. (University of Utah Press, 2024)
"A century ago, the Old Vero Site was brought to prominence by Elias Sellards upon his claim that the site contained early human remains associated with Pleistocene fauna. It was the first serious challenge to the belief, widely accepted until the Folsom discoveries in 1926, that humans had not entered Florida before the current Holocene geological epoch. The claim that human remains at the site were contemporary with late Ice Age animals stirred enduring controversy. Recent construction near the site resulted in new archaeological work being completed from 2014 to 2017. The Old Vero Site (8IR009) details the course of the recent re-excavations of the Old Vero Site while also summarizing the original excavations from a century ago. Additionally, the volume lays out the sequence and results of the recent project, using these new data to assess the accuracy of Sellards's assertions. This re-examination determined that Sellards's claims are not supported by the evidence. Adovasio, Hemmings, and Vento provide the data to settle the matter definitively: human remains at the site were intrusive from a later time horizon, as critics of the original work had vociferously argued"--
Keywords: Geschichte 2014-2017; Geschichte 1914-1917; Fund; Sachkultur; Archäologische Stätte; Ausgrabung; Indigenes Volk; Vero Beach, Fla.; Human remains (Archaeology) / Florida / Vero Beach; Indians of North America / Florida / Vero Beach / Antiquities; Prehistoric peoples / Florida / Vero Beach; Antiquities, Prehistoric / Florida / Vero Beach; Excavations (Archaeology) / Florida / Vero Beach; Prehistoric peoples / North America; Antiquities, Prehistoric / North America; Vero Beach (Fla.) / Antiquities; Antiquities; Antiquities, Prehistoric; Excavations (Archaeology); Human remains (Archaeology); Indians of North America / Antiquities; Prehistoric peoples; Florida / Vero Beach; North America